2006
DOI: 10.1016/j.ejheart.2005.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of the novel peptide apelin are decreased in patients with chronic heart failure

Abstract: Background: Apelin, the novel endogenous ligand for the G-protein-coupled receptor APJ, has shown positive inotropic, vasodilatory and diuretic properties in animal studies. Differential expression and synthesis of apelin and APJ receptors have been observed in normal and failing human hearts, suggesting a possible role in cardiovascular homeostasis. Changes in plasma apelin concentrations in relation to heart failure have been described in small studies with conflicting results. Our aim was to evaluate plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 26 publications
7
134
2
4
Order By: Relevance
“…The most important finding from our data is the negative, very strong correlation between serum levels of apelin-13 and NT-proBNP, which is in contradiction with other previous results [15], but in agreement with other scientific researches that showed lower apelin level in advanced heart failure, as well as with the theory that this decrease of serum apelin is negatively influenced by the course of the disease. Our findings showed that the Low apelin-13 group has higher NT-proBNP levels and also contains all the patients in NYHA IV class heart failure, 71% of the acute HF patients, and 7 of 8 patients who died before follow-up.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The most important finding from our data is the negative, very strong correlation between serum levels of apelin-13 and NT-proBNP, which is in contradiction with other previous results [15], but in agreement with other scientific researches that showed lower apelin level in advanced heart failure, as well as with the theory that this decrease of serum apelin is negatively influenced by the course of the disease. Our findings showed that the Low apelin-13 group has higher NT-proBNP levels and also contains all the patients in NYHA IV class heart failure, 71% of the acute HF patients, and 7 of 8 patients who died before follow-up.…”
Section: Discussioncontrasting
confidence: 56%
“…To our knowledge, there are no differences reported so far between genders, but already published studies either have a limited number of female subjects [15,[37][38][39], or the research focused mainly on male subjects [13,40]. The fact that there were no differences between genders other than apelin-13 level, NYHA class and LV mass and that apelin-13 was weakly correlated with LV mass when all subjects were analyzed (patients and controls) (Spearman's rho 0.28, p=0.023) give grounds for further research.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Yet its role is undetermined, as conflicting evidence has been found in KO studies, indicating both antagonistic and inducing roles for apelin in atherosclerotic formation (Hashimoto et al 2007. During heart failure, plasma apelin levels rise in the early stages of disease and stabilise or lower as the condition develops (Chen et al 2003, Chong et al 2006, Miettinen et al 2007). However, APJ mRNA is decreased in the weakened and enlarged heart of humans with idiopathic dilated cardiomyopathy (Foldes et al 2003).…”
Section: Cardiovascular Roles Of Apelin/apjmentioning
confidence: 99%